An Assessment of the Staff Strength of the University for Development Studies in the Light of the Standards Recommended by the National Council of Tertiary Education for Teaching Staff in Ghana's Public Universities - Kassim, Bawah A.; Abdallah, Yussif (Advances in Social Sciences Research Journal, 2021)
The paper examines the staff strength of the University for Development Studies (UDS) in the light of the standard recommended by the National Council of Tertiary Education (NCTE) for staffing in Ghana's public universities, with an emphasis on Teaching Staff (TS). The study uses the University's 2020/2021 Academic Year payroll data, which was analyzed with Microsoft Excel 2016 for Windows. The study found that, apart from the Lecturer rank that had a staff surplus of 65, the rest of the ranks consisting of Professor, Associate Professor and Senior Lecturer ranks did not meet the recommended standard by NCTE. The study also revealed that the number of female TS was much lower than that of their male counterparts for all ranks. The paper recommends that University Management should encourage all TS to publish more articles in reputable journals along with community service and teaching; in order to facilitate their promotion to higher ranks. The University should target candidates with final degrees for further recruitment in order to reduce the long waiting period required for staff with a master's degree to rise to higher ranks.